Issues of Data Visualization in the Educational Process - G. V.Yeldasheva (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses about visualization of information provided in the process of learning in the higher education system (lectures, seminars, theoretical materials for practical exercises).